2015
DOI: 10.1002/ep.12267
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the synergistic effect of porphyrin photosensitizer on graphene–TiO2 nanocomposite for visible light photoactivity improvement

Abstract: To use the visible light in photodegradation reactions efficiently, graphene–TiO2 nanocomposite was photosensitized using tetrakis(4‐carboxyphenyl)porphyrin. To investigate the effect of graphene as well as dye sensitization on the photoactivity of the synthesized photocatalyst, photocatalytic properties and photocurrent responses of the prepared samples were examined under visible light irradiation. A twofold increase of photocurrent response in the TG nanocomposite photosensitized with porphyrin (TGP) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…[32] and [33]. In literature, TiO 2 -graphene nanocomposite was also used for photocatalytic reactions under visible light and it was showed 93% degradation efficiency with a progress at photocatalytic activity studies [34].…”
Section: Introductionmentioning
confidence: 99%
“…[32] and [33]. In literature, TiO 2 -graphene nanocomposite was also used for photocatalytic reactions under visible light and it was showed 93% degradation efficiency with a progress at photocatalytic activity studies [34].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the spectra revealed that the degradation of MO by FZVN was considered to cleave the azo bond, consequently, led to the formation of the products and degradation of MO. The band appearing at 248 nm is possibly assigned to sulfanilic acid as compared with UV–vis spectra of the standard solution of sulfanilic acid (data not show), which is in accordance with nZVI degrading the azo dye . Therefore, sulfanilic acid was considered as one of intermediate of MO decolorization by FZVN.…”
Section: Resultsmentioning
confidence: 95%
“…Whereas, the average particle size was found to be 1.60 µm, as shown in Table 2. Rahimi et al, (2015) reported that the broad intense peak lower than 700 cm -1 corresponding to Ti-O-Ti vibration bands [19]. Rahim et al, (2016) reported that the weak absorption bands at 1620-1635 cm -1 and 3350-3450 cm -1 correspond to the bending and stretching vibrations of O−H, respectively [20].…”
Section: B Particle Size Distribution Of Cbtmentioning
confidence: 99%